2005
DOI: 10.1534/genetics.105.042861
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Instability Induced by Overexpression of DNA Ligase I in Budding Yeast

Abstract: Recombination and microsatellite mutation in humans contribute to disorders including cancer and trinucleotide repeat (TNR) disease. TNR expansions in wild-type yeast may arise by flap ligation during lagging-strand replication. Here we show that overexpression of DNA ligase I (CDC9) increases the rates of TNR expansion, of TNR contraction, and of mitotic recombination. Surprisingly, this effect is observed with catalytically inactive forms of Cdc9p protein, but only if they possess a functional PCNA-binding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 82 publications
3
55
0
Order By: Relevance
“…In vivo and in vitro data suggest that Pol δ may bind PCNA together with FEN1, whereas Lig1 binding is exclusive (9,20,21). In contrast, another in vivo study in mammalian cells has demonstrated that PCNA is stably associated with DNA, whereas its partners are transiently associated (22).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and in vitro data suggest that Pol δ may bind PCNA together with FEN1, whereas Lig1 binding is exclusive (9,20,21). In contrast, another in vivo study in mammalian cells has demonstrated that PCNA is stably associated with DNA, whereas its partners are transiently associated (22).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear how PCNA effects hand-off of DNA from polymerase and Fen1 to DNA ligase, thereby coordinating Okazaki fragments maturation. Biochemical studies have put forward a molecular tool-belt model, although this remains controversial [3][4][5]. However, recent biochemical studies [2] support a model where a single PCNA ring assembles an Okazaki fragment maturation complex composed of PolB1, Fen1 and Lig1.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that secondary structures can form in vivo and impair replication/repair enzymes. Studies in model organisms, such as S. cerevisiae, have shown that mutations in DNA replication enzymes, particularly Rad27 (yeast FEN-1 homolog), lead to TNR instability (6,(22)(23)(24)(25)(26)(27)(28). Rad27/FEN-1 is a multifunctional nuclease that plays a critical role in maintaining genome stability through RNA primer removal and long patch base excision repair.…”
mentioning
confidence: 99%